2022
DOI: 10.2147/ott.s386807
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitor Associated Clostridioides difficile Infection Among Patients with Lung Cancer

Abstract: Epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKIs)-associated Clostridioides difficile infection (CDI) among lung cancer patients have been reported in case reports and adverse events reporting system databases in the United States and Japan, but clinical data remained insufficient. This study aims to evaluate CDI in lung cancer patients receiving EGFR-TKIs. Methods: We conducted a retrospective cohort study using multi-institutional electronic medical records database. We included patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Blautia has been suggested to be abundantly reside in the intestine of neratinib-induced diarrhea rat model (Secombe et al, 2022). A retrospective clinical study by Chung et al showed that the use of first-generation EGFR-TKI increases the risk ofClostridioides difficile infection and diarrhea (Chung et al, 2022). Moreover, both loperamide and crofelemer group showed a significant increase in the abundance of Parasutterella as compared with that of the afatinib group.…”
Section: Transcriptomics Of the Ileum And Correlation With The Colon ...mentioning
confidence: 99%
“…Blautia has been suggested to be abundantly reside in the intestine of neratinib-induced diarrhea rat model (Secombe et al, 2022). A retrospective clinical study by Chung et al showed that the use of first-generation EGFR-TKI increases the risk ofClostridioides difficile infection and diarrhea (Chung et al, 2022). Moreover, both loperamide and crofelemer group showed a significant increase in the abundance of Parasutterella as compared with that of the afatinib group.…”
Section: Transcriptomics Of the Ileum And Correlation With The Colon ...mentioning
confidence: 99%
“…Therefore, only vancomycin is the preferred FDA approved drug for the treatment [ 15 - 16 ]. As the therapeutic antimicrobial options are limited for CDI due to its rising antibiotic resistance and declining sensitivity, there is an urgent need for the development of novel anti-clostridial drugs [ 17 , 18 , 19 , 20 , 21 ]. Five proteins of C difficile that were reported as drug targets were used [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging clinical evidence suggests TKIs could potentially have a protective role against CDI. In a study assessing the effect of anti-EGFR TKIs on CDI, lung cancer patients with diarrhea due to C. difficile had a longer interval between TKI initiation and diarrhea (median period: 75 days, range: 25 to 376 days) compared with patients who had diarrhea due to other causes (median period: 7 days, range: 0 to 49 days) [24]. The incidence of CDI in this study was 2.2%, which is notably lower compared to another study of cancer patients receiving immune checkpoint inhibitor immunotherapy where the incidence of CDI was 9.7% [25].…”
Section: Introductionmentioning
confidence: 99%